SIMBOL AGAMA DI RUMAH SEBAGAI PROSES TERAPEUTIK JIWA DALAM KELUARGA - Sabari Sabari (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The purpose of this study is to describe religious symbols that have a therapeutic effect on the soul in the family of the people of Sambas Regency. The results of this study are that religious symbols are a transcendent communication process that occurs between the owner of the house and the creator, namely Allah SWT in accordance with the meanings of Islamic religious symbols which are believed to be a teaching and have a function as remembrance (remembrance of Allah SWT and self-reflection so as to form self-concept that tends to be more calm, safe, peaceful, prosperous, and surrender to the creator.